Cambios en La Dinámica Familiar y Estrategias de Afrontamiento en 5 Militares Que Han Sufrido Amputación Por Map (2015)
The armed conflict in Colombia has led to the use of landmines, which are planted by subversive groups operating outside the law to harm the security forces. This paper describes the changes in family dynamics and coping strategies used by people who have lost members of his body. A qualitative methodology was used, from a semistructured interview applied to 5 members of the Colombian National Army affected by the situation described. Also it is emphasized that the disease is an event that not only brings physical changes in the individual that presents, but also emotional changes in your family, causing structural and functional changes in the system as the change in roles, hierarchies, communication and the responsibilities that members take to deal with the difficulty. In the same way more coping strategies used by these families are planning, acceptance of responsibility, positive evaluation and re seeking social support.